Inclusion in higher education: an exploration of the subjective experiences of students. Issue 2 (7th February 2021) - Tobbell, Jane; Burton, Rob; Gaynor, Andrea; Golding, Berenice; Greenhough, Kath; Rhodes, Christine; White, Stephen
ABSTRACT: There is a paucity of literature which explores students' subjective meanings of inclusion in higher education (HE). Much of the focus is on the social exclusion debate, where HE is seen as a mechanism for the promotion of social equality. There is some research which explores students' experiences, but this mostly involves those students who have acquired a label. Contemporary research in teaching and learning suggests that effective pedagogy should benefit all learners and should not require additional practices for separate groups. Based on this premise, this research seeks to begin an exploration of the meaning of inclusion to students participating in higher education. 251 students from a UK health and social science faculty participated in the research and responded to statements which elicited their subjective meanings of inclusion. Student understandings of inclusion are discussed through the emergent themes of 'the imperative of relationship' and 'flexible practice enables participation' and understood through the lens of socio-cultural theory.